Studies on the optimization of protease enzyme from Kesinai (Streblus asper) for milk coagulation - Seow, Yen Yi (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Streblus asper (Kesinai) leaves contain proteases that can be used to coagulate milk. The enzyme was extracted by using phosphate buffer at pH 7.2 and the extracted enzyme activity was tested for protease assay. Response Surface Methodology (RSM) using Two-Level Factorial and Central Composite Design (CCD) was used in screening and optimization of serine protease extraction from kesinai (Streblus asper) leaves respectively. The effect of independent variables, namely ratio of sample to buffer (1-5), weight of sample (10-50 gram) and mixing time (2-6 minutes) on proteases activity from kesinai leaves was investigated. The screening results showed that ratio sample to weight had the most significant effect (p<0.0001) on protease activity for enzyme extraction.activity was tested for protease assay. Response Surface Methodology (RSM) using Two-Level Factorial and Central Composite Design (CCD) was used in screening and optimization of serine protease extraction from kesinai (Streblus asper) leaves respectively. The effect of independent variables, namely ratio of sample to buffer (1-5), weight of sample (10-50 gram) and mixing time (2-6 minutes) on proteases activity from kesinai leaves was investigated. The screening results showed that ratio sample to weight had the most significant effect (p<0.0001) on protease activity for enzyme extraction.